ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI EFEKTIVITAS AUDIT INTERNAL : PERAN PENTING DUKUNGAN MANAJEMEN - Arles, Leardo; Anugrah, Rita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The purpose of this study to analyze factors affecting the Internal Auditeffectiveness. Specifically, this study examines the effects of competence andIndependence Internal Audit departement with management support as moderatevariabel. To test the hypotheses, a Partial Least Square analysis is applied toquestionnaire survey data from 80 respondents consist of Managers, InternalAuditors and Accountants in Bank Pembangunan Daerah (BPD) in Sumatera,Indonesia. As hypothesized, the result revealed the existence of a positive influenceof independence and management support on Internal Audit Effectiveness, butcompetence of Internal Audit not effect the likehood of Internal audit effectiveness.In addition, this research finding management support lower effect independence toInternal Audit effectiveness, but does not effect competence to Internal Auditeffectiveness.